Pendampingan Pengembangan Usaha Frozen Ayam Kampung UKM “Mbok Sri” Kabupaten Sukoharjo untuk Bangkit pada Pandemi Covid-19 - Wara Pratitis Sabar Suprayogi; Adi Ratriyanto; Dian Rachmawanti Affandi; Novi Akhirini; Agung Irawan (PRIMA: Journal of Community Empowering and Services, 2022)
Business Assistance for Household Frozen Ayam Ungkep Mbok Sri Sukoharjo Regency during the Covid-19 Pandemic. The Covid-19 pandemic has been impacting entrepreneurial sector, including micro, small, and medium enterprises (MSME) especially for food sector. This difficult situation requires MSME actors to adapt, including to make improvements in business management. “Mbok Sri” is spiced fried chicken producer located in Telukan Village, Grogol District, Sukoharjo Regency which has been running its business for four years with a production capacity of 400 birds/month. The Covid-19 pandemic situation has resulted in unstable demand and continuity of raw materials. Meanwhile, there are still many problems, including inadequate equipment facilities, unstandardized packaging for food, and no BPOM permit. The extention program was therefore aimed for: 1). Improvement of the clean, hygienic and comfortable place for the ungkep chicken production process, 2). Improvement of attractive product packaging with vacuum and labeling technology. The activities are carried out with assistance and guidance through Participatory Rural Appraisal (PRA), counseling so that MSME have hygienic business production houses and in accordance with BPOM standards, and digital marketing training. The result of this service is that business actors can carry out hygienic processing of chicken products with vacuum packaging and labels. In conclusion, this activity resulted in improvements of production houses and production process equipment with the increase of production capacity up to 512 birds/month or about to 28%.